Specialized High‐Protein Oral Nutrition Supplement Improves Home Nutrient Intake of Malnourished Older Adults Without Decreasing Usual Food Intake - Loman, Brett R.; Luo, Menghua; Baggs, Geraldine E.; Mitchell, Diane C.; Nelson, Jeffrey L.; Ziegler, Thomas R.; Deutz, Nicolaas E.; Matarese, Laura E. (My University, 2018)
Background: Reduced nutrient intake is common in patients after hospitalization, contributing to increased risk for readmissionand mortality. Oral nutrition supplements can improve nutrition status and clinical outcomes, but intake of food is prioritized byclinicians. This study examines the impact of a high-protein oral nutrition supplement (S-ONS) on nutrient intake post discharge. Methods: In a subset of patients (14 S-ONS and 16 placebo) from the NOURISH (Nutrition effect On Unplanned ReadmIssionsand Survival in Hospitalized patients) trial, 24-hour dietary recalls were conducted on 3 randomly selected days during the weeksof 30, 60, and 90 days post discharge. Nutrient intake was estimated using Nutrition Data System for Research software. Adequateenergy and protein intake were dened as 30 kcal/kg/d and 1.2 g/kg/d, respectively. Dietary Reference Intakes (DRIs) were usedfor other nutrients. Results: Less than half of patients met the requirements for energy, protein, and 12 micronutrients from foodintake alone during the study. Energy and protein intakes from food were not diminished relative to placebo. Considering nutrientintake from both food and S-ONS, 50% and 71% of patients receiving S-ONSs met energy and protein goals respectively at 90 days(compared with 29% and 36%, in the placebo group), and 100% met the DRI for total carbohydrate, iron, phosphorus, copper,selenium, thiamin, and riboavin at all time points, all of which were consumed at higher amounts vs placebo. Conclusion: Threemonths of S-ONS consumption increases intake of numerous nutrients without decreasing nutrient intake from food in oldermalnourished adults post discharge.
Keywords: malnutrition; minerals/trace element intake; nutrient intake; oral nutrition supplement; vitamin intake